Association between nighttime urinary frequency and sleep problems among Japanese adolescents. (17th November 2021) - Matsushima, Eriko; Otsuka, Yuichiro; Itani, Osamu; Matsumoto, Yuuki; Kaneita, Yoshitaka
Abstract : Objective: To conduct a cross‐sectional study to investigate the relationship between nighttime urinary frequency and sleep problems in Japanese adolescents. Methods: A self‐administered questionnaire survey was conducted among 1757 adolescents (mean age 15.6 ± 1.1 years; 49.0% boys). The survey assessed sleep problems (sleep duration, sleep quality, and insomnia symptoms), nighttime urinary frequency, eating habits (breakfast, late‐night eating, energy drink consumption), problematic internet use, engagement in club activities, and mental health. We analyzed the association between nighttime urinary frequency and sleep problems using descriptive statistics and logistic regression models. Results: The response rate was 99.6% (1699 students). The prevalence of nighttime urinary frequency ≥2 was 5.6% in boys and 4.6% in girls. The prevalence rates of sleep problems were: insomnia, 16.4%; difficulty initiating sleep, 11.8%; difficulty maintaining sleep, 5.9%; early‐morning awakening, 5.4%; and poor sleep quality, 19.9%. Analysis of the relationship with sleep problems differentiating between zero, one, and two nighttime urinations showed that an increase in nighttime urinary frequency corresponded to an increase in the prevalence of insomnia, difficulty initiating sleep, and difficulty maintaining sleep. Logistic regression analysis also showed that insomnia, difficulty initiating sleep, and difficulty maintaining sleep had a linear, significant relationship with increased nighttime urinary frequency. Conclusion: This study suggests that adolescents with high nighttime urinary frequency experience increased sleep problems. Consideration of urinary frequency is required when tackling adolescent sleep problems.